Preliminary investigation on the parasites and vibrio species of angelwing clam, Pholas orientalis - Gallaron, Clint Bryan M. (College of Fisheries, University of the Philippines, 1953)
The study was conducted to preliminary investigate parasites and vibrio flora that may possibly infect or infest the adults of oriental angel wing clam Pholas orientalis in their natural habitat. Three parasitic protozoans were discovered in the major tissues of the calm. Of these, ancistrocomids and unidentified stalked ciliates were present in the stomach, and unidentified circular ciliates inhabited the gill area in large number. Moreover, vibrio species had been found inside the digestive gland of p. orientalis. It was crudely characterized either as V. Alganolyticus or V. cholera. Overall, the presence of these parasites and vibrio appeared to have not harmed and infected major tissues of the clam. However, more in-depth research on the health management aspects of the clam including the larval and post-larval stages must be done.